Board Game Teaching the Fruit of the Spirit in Daily Life for Children - Amelinda Zabrina Iko Putri; T. Arie Setiawan Prasida; Jasson Prestiliano (Jurnal Ilmiah Sekolah Dasar, 2022)
The behaviour of Christian children, along with the times, does not reflect the behaviour of children who make religious values ​​a guide in everyday life. In addition, the fruit of the Spirit as a solution to the problem of Christian children's behaviour is not always taught in the environment around children. This study aims to develop a board game about the fruit of the Spirit as a guide for behaviour in daily life for children aged 10-12 years. This study uses the Research and Development with ADDIE model. The research subjects involved were elementary school teachers, pastors, parents, Sunday school seniors, fifth-grade elementary school children, and orphans. This study uses quantitative and qualitative data collection methods. The research instruments used were observations, interviews, literature studies, and questionnaires. The analytical method used is the descriptive qualitative method. The result of this research is that using board games as a medium for learning the fruit of the Spirit in daily life can make 89.7% of children understand the fruit of the Spirit better after playing the board game. Children become aware that the behaviour done so far does not reflect good and proper behaviour. Therefore, board games can be an effective and interesting learning medium for children aged 10-12 years to teach the fruit of the Spirit in daily life and make the fruit of the Spirit a behavioural guide in everyday life.